Self-regulation Learning, Feedback and Knowledge Transfer. Design Research with University Students - María Virginia Garello; María Cristina Rinaudo (Universidad Autónoma de Baja California, 2013)
This paper deals with the processes of self-regulation of learning, feedback and the transfer of academic knowledge in students majoring in education at the Universidad Nacional de Río Cuarto, Argentina. With the aim of impacting the acquisition of knowledge, the transfer of concepts in the field of teaching and the development of self-regulated learning, we applied, by means of design-based research methodology, two sequences of tasks that allowed us to analyze the answers that the students developed to complex problems similar to those they might face in their future professional practice. The theoretical framework of the study was structured based on current developments of the social constructivist approach of educational psychology. The joint analysis of the results shows the importance of giving university students assignments that employ the processes of interpretation and the transfer of problematic situations, group elaborations, and instances of feedback that permit the revision and improvement of answers.